Curcumin attenuates butter fat induced hyperlipidemia in mice: Curcumin attenuates hyperlipidemia (Journal of the Bangladesh Agricultural University, 2019)
Long-term intake of high-fat food disrupts lipid metabolism, resulting in fat accumulation, obesity, and hyperlipidemia. Curcumin, active ingredients of turmeric plants, has been shown to possess potent antioxidant and hypolipidemic properties. The study was conducted to observe the effects of curcumin on butter induced hyperlipidemia, hematological values and physio-pathological alterations in liver and aorta in mice. A total of 40 Swiss Albino mice (Mus musculus), aged 28-30 days with an average body weight of 27g were randomly divided into 2 groups. Group A was considered as non-treated control (NT) (n=8) and fed on standard mice pellet and fresh drinking water. Another group was considered as butter group (n=32), fed on standard mice pellet enriched with 10% butter and after 5 weeks, mice of butter group were subdivided into 4 equal groups (n=8). Group B was considered as butter treated (BT) group fed on standard mice pellet enriched with 10% butter. Group C (C1%), group D (C2%) and group E (C3%) fed on standard mice pellet enriched with 10% butter plus curcumin 1%, 2% and 3% in drinking water respectively. The experiment was carried out for period of another 10 weeks. Body weight gain of all mice was gradually increased and maximum weight gain was recorded in mice of butter fed group. Supplementation of curcumin to butter treated mice (group C, D and E) prevented weight gain. Mice treated with butter fat had significantly (p